Діяльність української еміграції в країнах Європи у міжвоєнний період ХХ ст. - Плазова, Т. І. (Видавництво Львівської політехніки, 2014)
Досліджується та аналізується питання діяльності української еміграції в країнах Європи в міжвоєнний період ХХ ст. Проаналізовано чисельність та соціальний статус української еміграції того періоду. Особливий інтерес становить завершальний етап визвольних змагань та перехід українського війська разом із державними органами в еміграцію за кордон. На сучасному етапі завданням є проаналізувати діяльність українських емігрантів за кордоном, їхні прагнення підтримувати дух національної свідомості, дослідити їхній вплив на подальший розвиток ідеї боротьби за незалежність на теренах України, адже згодом саме ці люди долучилися до активних дій у відстоюванні суверенності України в роки Другої світової війни. This article investigates and analyzes the issue of Ukrainian emigration in Europe in the interwar period of the twentieth century, also – the number and social status of Ukrainian emigration in the period. At the turn of the 20–30s of the twentieth century there were finally decided the main centers of concentration of Ukrainian political emigration in Europe. They became centers of Ukrainian political thought outside Ukraine, and their activities are reminded of the existence of the Ukrainian people. It should be noted that in most European countries in general knew little about Ukraine, did not perceive it as a geopolitical unit and not bother Ukrainian question. Views on Ukrainians as a phenomenon insignificant is consistent with the concept of proimperial measures for the development of colonial territories as those that are incapable of independent statehood. Development of Ukraine as an independent and democratic state is not possible without a comprehensive and detailed study of its history. Of particular interest is attracting the final stage of the struggle for liberation and transition Ukrainian troops together with the authorities to emigrate abroad. It is at present the task to analyze the activity of Ukrainian emigrants abroad, their desire to maintain the spirit of national consciousness and explore their impact on the further development of the idea of the struggle for independence in Ukraine. Great importance and how they passed on to their descendants love Ukraine and the desire to see this great country free from Russia’s power and sovereign. After 1991 the historiography situation radically changed in Ukraine: established the spirit of pluralism in scientific work, changed priorities, methodology and research methods, the researchers had access to previously banned archival materials, some of which have returned from abroad. It is through archival documents can reliably reproduce the events of those times, including being Ukrainian political emigration in the European inter-war period. At the present stage for Ukrainian scientists are challenged to analyze the activity of Ukrainian emigrants abroad, their desire to maintain the spirit of national consciousness and explore their impact on the further development of the idea of the struggle for independence in Ukraine. Of great importance is the fact that how they passed on to their descendants love Ukraine and the desire to see this great country free from Russia’s power and sovereign.
Keywords: національна свідомість; Друга світова війна; українська еміграція; країни Європи; українське військо; Ukrainian emigration; Ukrainian army; Second world War; national consciousness; countries of Europe